The perceived impact of services rendered by Lay Counsellors - Stanbury, Claire (My University, 2007)
The aim of this exploratory study was to determine whether victims of crime who have encountered face-to-face interventions with lay counsellors, perceive these interventions as helpful, hindering or having no effect on their ability to cope after a traumatic incident. Five participants were selected for this qualitative study. A semi-structured interview schedule was constructed by the researcher to guide the interview process and thematic content analysis was used to analyse the data. The main emergent themes related to symptoms experienced by participants, time, victim support centres, perceptions of lay counsellors, short-term interventions, the model used and the participants overall perceptions of the services rendered by lay counsellors. Although the results were too varied to conclude the perceived effectiveness of interventions, the results are invaluable in gaining an in-depth understanding of the perceived impact of the services rendered by lay counsellors and what factors influence these perceptions.
Student Number : 0009222T - MA research report - School of Human and Community Development - Faculty of Humanities
Keywords: trauma; lay counsellors; victims of crime; debriefing; victim support; WITS trauma intervention model; crime in South Africa